2002
DOI: 10.1046/j.1365-2958.2002.03117.x
|View full text |Cite
|
Sign up to set email alerts
|

The LuxR family protein SpnR functions as a negative regulator of N‐acylhomoserine lactone‐dependent quorum sensing in Serratia marcescens

Abstract: SummarySerratia marcescens SS-1 produces at least four N -acylhomoserine lactones (AHLs) which were identified using high-resolution mass spectrometry and chemical synthesis, as N-(3-oxohexanoyl) homoserine lactone (3-oxo-C6-HSL), N -hexanoyl-(C6-HSL), N -heptanoyl (C7-HSL) and N -octanoyl-(C8-HSL) homoserine lactone. These AHLs are synthesized via the LuxI homologue SpnI, and regulate via the LuxR homologue SpnR, the production of the red pigment, prodigiosin, the nuclease, NucA, and a biosurfactant which fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
135
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(142 citation statements)
references
References 71 publications
4
135
1
Order By: Relevance
“…SpnI/SpnR C6 HSL, C7HSL, C8HSL, 3OC6HSL Sliding motility, biosurfactant production; prodigiosin and nuclease production [170] Serratia plymuthica…”
Section: Ss-1mentioning
confidence: 99%
See 1 more Smart Citation
“…SpnI/SpnR C6 HSL, C7HSL, C8HSL, 3OC6HSL Sliding motility, biosurfactant production; prodigiosin and nuclease production [170] Serratia plymuthica…”
Section: Ss-1mentioning
confidence: 99%
“…In AI-2 dependent multispecies biofilm communities, suppression of luxS gene expression is expected to lead to variation in interspecies behavior [170][171][172].…”
Section: Mutationsmentioning
confidence: 99%
“…No evidence of an AHL-dependent quorum-sensing system controlling pigment biosynthesis has been found in any of the other 22 S. marcescens strains tested, of which seven are pigmented (data not shown), implying that quorum-sensing control of prodigiosin production is both highly strain dependent and comparatively rare. Interestingly, a recent report has described a strain of S. marcescens in which pigment is affected by production of OHHL, another AHL (Horng et al, 2002). Where AHLs are made by S. marcescens strains, BHL is usually the molecule produced.…”
Section: Differences In Pig Cluster Regulationmentioning
confidence: 99%
“…It has been suggested that EsaR represses the synthesis of extracellular polysaccharide at low cell density, and that the presence of its cognate signal molecule in micromolar amounts results in derepression (Beck von Bodman & Farrand, 1995;Beck von Bodman et al, 1998;Minogue et al, 2002). Other examples of R-proteins that have been proposed to function as repressors include SpnR of Serratia marcescens and YpsP of Yersinia pseudotuberculosis (Atkinson et al, 1999;Horng et al, 2002).The AHL-producing phenotype is widespread among members of the Enterobacteriaceae (e.g. Serratia liquefaciens, Enterobacter agglomerans, Erwinia carotovora, Hafnia alvei and Rahnella aquatilis) Swift et al, 1993Swift et al, , 1999.…”
mentioning
confidence: 99%